Chemical waste risk reduction and environmental impact generated by laboratory activities in research and teaching institutions - Elizabeth de Souza Nascimento; Alfredo Tenuta Filho (Universidade de São Paulo, 2010)
The environmental impact caused by teaching and research with regard to chemical waste is of increasing concern, and attempts to solve the issue are being made. Education and research-related institutions, in most laboratory and non-laboratory activities, contribute to the generation of small quantities of waste, many of them highly toxic. Of this waste, some is listed by government agencies who are concerned about environmental pollution: disposal of acids, metals, solvents, chemicals and toxicity of selected products of synthesis, whose toxicity is often unknown. This article presents an assessment of the problem and identifies possible solutions, indicating pertinent laws, directives and guidelines; examples of institutions that have implemented protocols in order to minimize the generation of waste; harmonization of procedures for waste management and waste minimization procedures such as reduction, reuse and recycling of chemicals. O impacto ambiental acarretado por atividades de pesquisa e ensino no que se refere aos resíduos químicos vem sendo cada vez mais discutido e tentativas de solucionar a questão vêm sendo apresentadas. As instituições de ensino e pesquisa, em quase todas as atividades e não somente as laboratoriais, contribuem para a geração de pequenas quantidades de resíduos, muitos deles altamente tóxicos. Destes, alguns constam em listas de agências governamentais que se preocupam com a qualidade do meio ambiente: descartes de ácidos, metais, solventes, agentes químicos de elevada toxicidade e ainda os produtos de síntese, cuja toxicidade é frequentemente desconhecida. Este artigo apresenta uma avaliação do problema identificando possíveis soluções, a partir da apresentação de legislações pertinentes, exemplos de instituições que vêm implantando protocolos que minimizam a geração de resíduos, sistemas de harmonização de processos de gerenciamento de resíduos e procedimentos de minimização de resíduos, como a redução, reutilização e reciclagem dos produtos químicos.